Evaluation of exotic sorghum germplasm lines for yield and adaptation in the Semi-Arid Region of Limpopo Province (Mankweng), South Africa - Kgasago, Matlale Moipone (My University, 2023)
Sorghum (Sorghum bicolor (L.) is a grass that is grown for its grain, and is an essential crop, which can be used as a staple food for humans and livestock. It can adapt to drought, salinity, and high temperatures which makes it best suited for future climate change. Sub-Saharan Africa (SSA) is facing a challenge of food insecurity and drought, and sorghum is one of the cereal crops in SSA’s food value chain, and effective production, especially by smallholder farmers, will reduce these problems. Sorghum is regarded as a stable crop across the African continent and it is rich in nutrients. 13 exotic sorghum germplasm for evaluation for adaptation and yield in South Africa were introduced to reduce food insecurity with nutritious sorghum. The experiment was conducted at the University of Limpopo farm (Syferkuil), and was laid down in an incomplete block design with three replications and 17 varieties of exotic sorghum germplasm, which were planted in two seasons, 2021 and 2022, to check the adaptation, yield, and nutrient content of the varieties and these were compared with the check line from South Africa (Pan 606). The results show that some of these varieties performed better than the check line. There was a significant difference (P<0.05) obtained among varieties in both 2021 and 2022 for 200 seed weight, and the test lines (Fara Kano, ICSG1780727) performed better than the check line in both seasons. Again, there was a significant difference (P<0.05) obtained among the varieties in calcium and sodium. ICSG 1780724 and Yarlabe performed above the control in the concentration of sodium while the performance of all the test lines was above the check line on the concentration of calcium. The varieties, which performed better than the check line, can be used by breeders to improve the different traits and be released for smallholder farmers’ cultivation
Thesis (M. Agricultural Management (Plant Production)) -- University of Limpopo, 2023
Keywords: Germplasm; Adaptation; Yield sub – Saharan Africa; Climate change adaptation; Food security; Sorghum; Food security; Sorghum as food; Climatic changes; Climatic changes -- South Africa